Evaluation of transmasseteric anteroparotid approach to mandibular subcondylar fractures - Mohamed, Ahmed Mohamed Hosni; Elfar, Ahmed Mohammed Mostafa; Khallaf, Mustafa G; Sapri, Ahmed Mohammed Saaduddin; Omar, Mohamed R; Mahmoud, Nermine Ramadan (International journal of health sciences, 2021)
Introduction: Different techniques employing, retromandibular, preauricular, or submandibular incisions have been used for the treatment of subcondylar and condylar fractures. The approaches listed above may lead to some disadvantages which include limited visibility, facial nerve damage, and problems associated with the parotid gland. Study objective: Clinically, case studies were performed to evaluate the efficacy of P-TMAP approach for open reduction and internal fixation (ORIF) of condylar and subcondylar fractures. The study comprised of 7 people within the condylar and subcondylar fractures group who were treated by ORIF. We analyzed the administrative hours, accessibility, and medical review on perioperative complications. A CT scan was done to confirm the site where condylar fractures were reduced. Findings: Visibility and accessibility were good. The patients underwent careful anatomical alignment and stabilization. These reported complications were limited and only lasted temporarily. The facial nerve (buccal branch) palsy of one patient was the only adverse event that was reported, and it resolved spontaneously in 3 months. No case of Frey's syndrome and sialocele was spotted. Conclusion: The P-TMAP method is an effective way of access for closing the reduction and fixing the condylar fractures. It facilitates retention, transference, relocation, and fixation of the condyle.